2017
DOI: 10.1016/s2095-3119(16)61550-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of duck plague virus glycoprotein C in viral adsorption: Absence of specific interactions with cell surface heparan sulfate

Abstract: Many mammalian herpes viruses utilize heparan sulfate (HS) moieties present on cell surface proteoglycans as receptors for cell entry, and this process also requires viral glycoprotein C (gC) homologues. However, our understanding of the role of gC in facilitating attachment of other alpha-herpes viruses such as the duck plague virus (DPV) remains preliminary. To study the role of gC during DPV infection, we used a gC-deleted mutant virus (DPV-ΔgC-EGFP). Examination of the viral copy number by real-time PCR, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…However, previously studies about DPV focused on the epidemiology and prevention, instead of the studying of molecular biology and the function of glycoproteins 5 . To date only a few gens such as gC and gE from DPV have been addressed by studying mutant viruses 12 , 13 . gC involved in alphaherpesvirus adsorption were present in the DPV genome and relatively conserved, but the function of DPV gC also makes a difference with other alphaherpesvirus, which is independent of interaction with heparin sulfate of cell surface 12 , 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previously studies about DPV focused on the epidemiology and prevention, instead of the studying of molecular biology and the function of glycoproteins 5 . To date only a few gens such as gC and gE from DPV have been addressed by studying mutant viruses 12 , 13 . gC involved in alphaherpesvirus adsorption were present in the DPV genome and relatively conserved, but the function of DPV gC also makes a difference with other alphaherpesvirus, which is independent of interaction with heparin sulfate of cell surface 12 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…To date only a few gens such as gC and gE from DPV have been addressed by studying mutant viruses 12 , 13 . gC involved in alphaherpesvirus adsorption were present in the DPV genome and relatively conserved, but the function of DPV gC also makes a difference with other alphaherpesvirus, which is independent of interaction with heparin sulfate of cell surface 12 , 14 . Therefore, although alphaherpesvirus share many common strategies for their replication cycle 15 , they also keep some individually patterns to invade and infect target cells.…”
Section: Introductionmentioning
confidence: 99%
“…The target segment (UL13 left arm-FRT-Kan-FRT-UL14 right arm) was PCR-amplified using the ΔUL13&UL14 F F/R primers (Table 2). Then, the infectious clone DEV CHv-ΔUL13&UL14-G was generated by employing a recombinating system based on the genetic manipulation of the DEV CHv-G infectious clone [34][35][36][37]. Briefly, the pKD46 plasmid, which encodes the recombination genes exo, beta, and gam under the tight control of a ParaB promoter, was first introduced into E. coli DH10B containing the DEV CHv-G plasmid by electrophoretic transfer.…”
Section: Construction Of Recombinant Viruses Dev Chv-ul13δnlsmentioning
confidence: 99%
“…The properties of some DEV genes have been preliminary characterized [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. We previously reported that DEV UL47-encoded protein (pUL47) modulates the distribution of UL41-encoded protein (pUL41) [37].…”
Section: Introductionmentioning
confidence: 99%